SHARIA INSURANCE COMPANY BUSINESS MANAGEMENT MODEL IN THE DIGITAL 4.0 ERA - Renny Oktavia; M. Taufiq (Institut Agama Islam Negeri Madura, 2021)
This study aims to determine how the business management model of Islamic insurance companies in the digital era 4.0. The research method used is a qualitative research method using the Grounded Theory approach. The results of this study explain that, in running the insurance business in the era of revolution 4.0 implementing a supporting system, it is a combination of four components, namely: insurance / financial literacy, network marketing, human technology, and digital technology. The four components are driven by three mechanisms, namely: digital funneling, learning models, gamification systems, to achieve targeted business results. Keywords: Insurance Business, Sharia Insurance, Digital Technology